Exploring Effective ICT Integration Strategies in Education: A Case of Two Public Primary Schools in Mombasa, Kenya - Haji, Juma R.; Shiyo, Rose J.; Mrutu, Nipael E. (Journal of Education and Practice, 2023)
Purpose: The contemporary education landscape is undergoing a significant transformation, largely driven by the integration of Information and Communication Technologies (ICT). This paper explores the experiences of educators as they incorporate ICT into teaching and learning. Methodology: The study was conducted in Mombasa City, Kenya, and utilized qualitative research methods, including in-depth interviews, focus group discussions, and classroom observations, in a case study design involving two urban primary schools. The research meticulously documented the experiences of 16 participants. Findings: The findings of the study highlight several advantages of using ICT in teaching and learning, including easy access to information, interactive and personalized learning opportunities, as well as collaboration. However, the data also revealed significant challenges faced by educators, such as unstable electricity, inadequate ICT gadgets, internet fluctuation, and a lack of skills to integrate ICT into teaching. Unique Contribution to Theory, Policy, and Practice: Educators consistently stressed the importance of continuous support and professional development to enhance their ICT integration skills. Furthermore, the research emphasized several promising recommendations, including the installation of alternative sources of electricity, sourcing for additional ICT devices, supervising learners while using ICT gadgets, and conducting professional development initiatives tailored to the creation of a collaborative community of practice (COP), which have the potential to effectively address these challenges. To fully leverage the potential of ICT for enriching the learning experience, equipping students with essential digital skills, and preparing them for a digital-centric world, educational institutions, and policymakers must prioritize investments in technological infrastructure and foster a culture of innovation and collaboration among educators.